Imperfect Private Information in Insurance Markets - Solomon, Adam (The Review of Economics and Statistics, 2026)
This paper studies imperfectly perceived private information in insurance markets when contracts endogenously respond. Equilibrium contracts, pooling, and welfare depend on the joint distribution of risk and misperception. In the Health and Retirement Study (HRS), I show that misperceptions typically covary with (medical, long-term care, disability, and mortality) risk type: high types underperceive their risk and low types overperceive. I develop a general model and algorithm to estimate the equilibrium contracts, pooling, and welfare impact of misperceptions that is applicable in many settings. I offer suggestive evidence from U.S. annuity markets that contracts are distorted due to misperceptions, with welfare likely increasing.